Households' participation in community-based solid waste management program - Camayra, Zylette G.
Proper management of solid waste is the answer to the worsening problem of garbage. The participation of the household sector, as the primary source of solid waste, plays an important role in the successful implementation of Community-Based Solid Waste Management Program )CBSWMP)., The study aims to determine whether there is a relationship between households' participation in Community-Based Solid Waste Management Program and the age and awareness of the household head as well as the monthly income of the household. It seeks to accomplish the following objectives: (1) To describe the profile of the households in barangay Mat-y, Miag-ao, with active CBSWMP; (2) To determine if there is a relationship between households' participation in CBSWMP and age of the household head; (3) To determine if there is a relationship between households' participation in CBSWMP and income of the household; (4) To determine if there is a relationship between households' participation in CBSWMP and awareness of the household head. The sample of the study involved residents of barangay Mat-y, Miaga-ao. Eighty respondents, from the total 320 probable respondents, were randomly selected and interviewed. The interview was made possible using an interview schedule. Statistical analysis of the data revealed that, age, monthly income and level of awareness did not show direct correlation with respondents' participation with CBSWMP. although, a relationship exists among variables and participation on CBSWMP, the nature of relationship is weak and inverse thereby not giving significant findings. From the results, it can be said therefore that, the participation of househodls in CBSWMP may depend on households' attitudes and behavior towards the program. The researchers recommend further research to be conducted on households' participation in CBSWMP but using the variables not included in the study.